Investigation of Fresh, Mechanical, and Durability Properties of Rubberized Fibre-Reinforced Concrete Containing Macro-Synthetic Fibres and Tyre Waste Rubber - Nusrat Jahan Mim; Mizan Ahmed; Xihong Zhang; Faiz Shaikh; Ahmed Hamoda; Vipulkumar Ishvarbhai Patel; Aref A. Abadel (Buildings)
The growing disposal of used tyres and plastic waste in landfills poses a significant environmental challenge. This study investigates the potential of utilizing used tyre rubber and macro-synthetic fibres (MSFs) made from recycled plastics in fibre-reinforced rubberized concrete (RuFRC). Various percentages of tyre rubber shreds were used to replace coarse aggregates, calculated as 10%, 20%, and 30% of the volume of fine aggregates; fibre dosages (0%, 0.25%, 0.5%, 0.75%, and 1% by volume) were incorporated into the mix, and a series of physical, mechanical, and durability properties were evaluated. The results show that, as the fibre and rubber content increased, the slump of RuFRC decreased, with the lowest value obtained for concrete with 1% fibre and 30% rubber. The density of RuFRC decreases as the rubber percentage increases due to air voids and increased porosity caused by the rubber. The strength properties of RuFRC were found to decline with the increase in the rubber content, with mixes containing 30% rubber exhibiting reductions of about 60% in compressive strength, 27% in tensile strength, and 13% in flexural strength compared to the control specimen. Durability testing revealed that an increased rubber content led to higher water absorption, water penetration, and chloride ion permeability, with 30% rubber showing the highest values. However, lower rubber content (10%) and higher fibre dosages improved the durability characteristics, with water absorption reduced by up to 5% and shrinkage strains lowered by about 7%, indicating better compaction and bonding. These results indicate that RuFRC with moderate rubber and higher fibre content offers a promising balance between sustainability and performance.